Pengaruh Penggunaan Social Media Marketing dan Content Marketing terhadap Brand Awareness di Institusi Pendidikan - Fakhrul Hilman Ramadhan (Syntax Corporation Indonesia, 2024)
The purpose of this study is to evaluate the implementation of social media, content marketing, and brand awareness at the Bandung Culinary Academy and analyze the influence of each and the combination of the two on brand awareness. This research was conducted using an explanatory research approach. In this study, the research object consists of 2 (two) types of variables, namely independent variables and dependent variables. This study uses 2 (two) independent variables, namely the use of social media marketing (X1) and the use of content marketing (X2). The bound variable used in this study is brand awareness (Y). As a result, ATB Bandung has not done social media marketing well, especially in terms of communicating the products offered, but the value of the products offered can be conveyed well to the public. Although the content marketing carried out by ATB Bandung is interactive, relevant, and easy to understand.